PRACTICAL STUDY ON THE CFRP REINFORCEMENT - Catalina IANASI (Fiabilitate şi Durabilitate)
One of the defining goals of this paper is getting new resistant material which combine the qualities of basic materials that get into its composition but not to borrow from them their negative properties. In recent years, carbon fiber composites have been increasingly used in different ways in reinforcing structural elements. Specifically, the use of CFRP composite materials as reinforcement for wood beams under bending loads requires paying attention to several aspects of the problem which are presented in this paper.